Oligoarginine vectors for intracellular delivery: Role of arginine side-chain orientation in chain length-dependent destabilization of lipid membranes - Bouchet, Ana María (2012)
Arginine-rich peptides receive increased attention due to their capacity to cross different types of membranes and to transport cargo molecules inside cells. Even though peptide-induced destabilization has been investigated extensively, little is known about the peptide side-chain and backbone orientation with respect to the bilayer that may contribute to a molecular understanding of the peptide-induced membrane perturbations. The main objective of this work is to provide a detailed description of the orientation of arginine peptides in the lipid bilayer of PC and negatively charged PG liposomes using ATR-IR spectroscopy and molecular modeling, and to relate these orientational preferences to lipid bilayer destabilization. Molecular modeling showed that above the transition temperature arginine side-chains are preferentially solvent-directed at the PC/water interface whereas several arginine side-chains are pointing towards the PG hydrophobic core. IR dichroic spectra confirmed the orientation of the arginine side chains perpendicular to the lipid-water interface. IR spectra shows an randomly distributed backbone that seems essential to optimize interactions with the lipid membrane. The observed increase of permeation to a fluorescent dye is related to the peptide induced-formation of gauche bonds in the acyl chains. In the absence of hydrophobic residues, insertion of side-chains that favors phosphate/guanidium interaction is another mechanism of membrane permeabilization that has not been further analyzed so far.